2018
DOI: 10.1002/smll.201800652
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic and Magnetic Resonance Imaging Bimodal Contrast Agent Displaying Amplified Photoacoustic Signal

Abstract: Progress in photoacoustic (PA) and magnetic resonance imaging (MRI) bimodal contrast agents has been achieved mainly by utilizing the imaging capability of single or multiple components and consequently realizing the desired application for both imaging modalities. However, the mechanism of the mutual influence between components within a single nanoformulation, which is the key to developing high‐performance multimodal contrast agents, has yet to be fully understood. Herein, by integrating conjugated polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…Figure 3 B shows the PA images of the microdroplets in tubes. The PA effects were activated by the laser pulse at 750 nm, which is the absorption peak of CP NPs 24 . The irradiation energy is 4.7 mJ/pulse for subfigure a) and 14 mJ/pulse for subfigure (b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 B shows the PA images of the microdroplets in tubes. The PA effects were activated by the laser pulse at 750 nm, which is the absorption peak of CP NPs 24 . The irradiation energy is 4.7 mJ/pulse for subfigure a) and 14 mJ/pulse for subfigure (b).…”
Section: Resultsmentioning
confidence: 99%
“…S3 ), the microdroplets were further tested in vivo in healthy animals by injecting via tail vein and keeping the animals under consistent monitoring for over 15 min to ensure the safety of the three layer structures. The cell toxicity and animal experiments of the CP NPs have been conducted by the previous researches 24 , 25 , and thus were not repeated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides nanostructures, that is, the physical arrangement of different components within a single nanoagent, could also lead to distinct or superior PA performance due to synergy or enhancement in the photothermal generation capability. For instance, it has been reported that the increased iron oxide ratio of the conjugated polymers PDPP3T/iron oxide coencapsulated NPs could amplify the PA signal by generating additional heat and dissipating the heat produced in a faster manner 75 . Furthermore, the distribution of iron oxide NPs and organic molecules in the formed nanostructure was also reported to affect the PA signal (Figure 9).…”
Section: Design Considerations Of Pa Contrast Agents For Brain Imagingmentioning
confidence: 97%
“…These properties explain the use of IONPs in all major imaging techniques, with examples in OI [37], PAI [38], SPECT [39], PET [30] and MRI [36], and magnetic resonance imaging [35,40,41]. MRI deserves special mention since it is the most commonly used imaging technique with IONPs due to their magnetic properties.…”
Section: Introductionmentioning
confidence: 99%